2017
DOI: 10.1177/0741932517713310
|View full text |Cite
|
Sign up to set email alerts
|

Variability in DIBELS Next Progress Monitoring Measures for Students at Risk for Reading Difficulties

Abstract: Previous research on curriculum-based measurement of oral reading fluency (CBM ORF) found high levels of variability around the estimates of students’ fluency; however, little research has studied the issue of variability specifically with well-designed passage sets and a sample of students who scored below benchmark for the purpose of progress monitoring. We examined the variability in oral reading fluency score slopes due to passage and student characteristics using DIBELS Next progress monitoring passages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…M. Shinn & Shinn, 2002) and, more recently, including the use of readability formulae, field-testing, and statistical equating to decrease passage variability (Ardoin & Christ, 2009; Christ & Ardoin, 2009; Poncy et al, 2005; Powell-Smith, Good, & Atkins, 2010). In spite of these actions, some passage-level variability remains (Briggs, 2011; O’Keeffe et al, 2017). In particular, research has indicated that there are differences in difficulty level between narrative and expository passages at the same reading level, but there is not a consensus regarding which type of passage tends to be more difficult (Briggs, 2011; O’Keeffe et al, 2017).…”
Section: Sources Of Variabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…M. Shinn & Shinn, 2002) and, more recently, including the use of readability formulae, field-testing, and statistical equating to decrease passage variability (Ardoin & Christ, 2009; Christ & Ardoin, 2009; Poncy et al, 2005; Powell-Smith, Good, & Atkins, 2010). In spite of these actions, some passage-level variability remains (Briggs, 2011; O’Keeffe et al, 2017). In particular, research has indicated that there are differences in difficulty level between narrative and expository passages at the same reading level, but there is not a consensus regarding which type of passage tends to be more difficult (Briggs, 2011; O’Keeffe et al, 2017).…”
Section: Sources Of Variabilitymentioning
confidence: 99%
“…In spite of these actions, some passage-level variability remains (Briggs, 2011; O’Keeffe et al, 2017). In particular, research has indicated that there are differences in difficulty level between narrative and expository passages at the same reading level, but there is not a consensus regarding which type of passage tends to be more difficult (Briggs, 2011; O’Keeffe et al, 2017). Publishers continue to include both narrative and expository passages to increase the validity of their passage sets for monitoring progress toward important goals, which would presumably include the ability to read and comprehend narrative and expository text.…”
Section: Sources Of Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in WRCM scores across time are not solely attributable to meaningful changes in oral reading rate. The manner in which probes are constructed (Christ & Ardoin, 2009; Hintze & Christ, 2004), differences in difficulty among passage sets (Betts, Pickart, & Heistad, 2009; Cummings, Park, & Bauer Schaper, 2013; Francis et al, 2009), the type of passage (e.g., expository vs. narrative; O’Keeffe, Bundock, Kladis, Yan, & Nelson, 2017), the manner in which instructions are delivered (Christ, White, Ardoin, & Eckert, 2013; Colon & Kranzler, 2006), the setting in which data are collected (Derr & Shapiro, 1989), and errors committed by data collectors (Cummings, Biancarosa, Schaper, & Reed, 2014) all influence the observed WRCM for a student at any given point in time. Further, it is likely that idiosyncratic differences in the testing environment and disposition of the student may contribute to minor fluctuations in performance.…”
Section: Cbm-rmentioning
confidence: 99%